A series of phenyl sulfonate metal coordination polymers as catalysts for one-pot Biginelli reactions under solvent-free conditions - Wang, J.H.; Tang, G.M.; Wang, Y.T.; Cui, Y.Z.; Wang, J.J.; Ng, S.W. (Royal Society of Chemistry, 2015)
Three new metal coordination polymers, namely, [Co(DPP)2(H2O)2]·(BS)2·2H2O (1), [Co(DPP)2(H2O)2]·(ABS)2·2H2O (2) and [Co(DPP)2(MBS)2] (3) [DPP = 1,3-di(pyridin-4-yl)propane, BS = phenyl sulfonic acid, ABS = p-aminobenzene sulfonic acid, MBS = p-methylbenzene sulfonic acid] were obtained under hydrothermal conditions. Complexes 1-3 were structurally characterized using X-ray single-crystal diffraction, XRD and IR spectroscopy. Both complexes 1 and 2 display a 1D tape structure. Meanwhile, complex 3 exhibits a 2D layer and further stacks via C-H⋯π interactions to generate a three-dimensional supramolecular architecture. These three metal coordination polymers have been applied as catalysts for the green synthesis of a variety of 3,4-dihydropyrimidin-2(1H)-ones under solvent-free conditions through the Biginelli reaction. Interestingly, the catalysis products have been obtained in high yields under eco-friendly synthesis conditions.